DURATION RELATIONSHIP HELP DAMAGE OF PATIENTS WITH STROKE NEOROLOGICAL IN ULIN HOSPITAL BANJARMASIN - M. Sobirin Mohtar (Universitas Sari Mulia, 2020)
Background: Stroke is the second leading cause of death in the world. One of the key in minimizing brain damage caused by stroke is to provide fast and precise handling. Neurological damage in stroke patients can be measured using the NIHSS. Aim: Knowing the duration of the relationship with the degree of damage neorological help stroke patients in Ulin Hospital Banjarmasin. Method: The method used is quantitative cohort approach. Total Population 177 stroke patients with an average of 59 patients. Samples taken as many as 51 patients with purposive sampling techniques and sample size calculations through Solvin formula. Analyzed using univariate and bivariate analysis through Spearman rank test. Results: The results showed the p value in the duration of the aid with the score of NIHSS at 24 hours (p = 0.000), 48 hours (p = 0.000) and 72 hours (p = 0.000), which means that less than 0.005 indicate that the correlation between the duration of the aid and the extent of damage neorological meaningful. While the average level of damage neorological at 24 hours (0.912), 48 hours (0.852), 72 hours (0.827) which, if seen from the area of relationship strength values were in the range 0.76 to 1.00, which means the correlation is very strong. Conclusion: There is a relationship duration neorological help with the damage level of stroke patients in Ulin Hospital Banjarmasin. Keywords: The duration of the aid, the level of damage neorological, stroke patients.